Persistent racial and ethnic inequities in cancer-specific mortality of head and neck cancers by human papillomavirus infection. Issue 28 (1st October 2022) - Abdelaziz, Abdullah Islam; Calip, Gregory Sampang
Abstract : 148 Background: Overlapping racial and ethnic disparities exist in the prevalence of risk factors that drive the prognosis of head and neck cancers in the US, including the use of tobacco products, socioeconomic status and human papillomavirus (HPV) infection. Our objective was to describe inequities in cancer-specific survival among patients diagnosed with head and neck cancers by HPV status and racial/ethnic group. Methods: We conducted a retrospective cohort study using the Surveillance, Epidemiology and End Results Head and Neck with HPV Status Database. Patients diagnosed with first primary cancers of the hypopharynx, nasopharynx, oropharynx, pharyngeal tonsil, other pharyngeal, soft palate and tongue base between 2010 and 2016 were included, and information on clinical and demographic characteristics including tumor information, cancer-directed treatment, area-level socioeconomic status and HPV status were collected from population-based cancer registry data. Estimates of 5-year cancer-specific survival were calculated using the Kaplan-Meier method, and multivariable Cox proportional hazards models were used to estimate adjusted hazard ratios (HR) and 95% confidence intervals (CI) for racial/ethnic inequities in survival stratified by HPV status. Results: Among 15, 393 patients diagnosed with head and neck cancer with documented HPV status, the median age was 59 years (interquartile range 53-66) and 10, 457 (68%) were HPV+. Compared to patients diagnosed with HPV- head and neck cancers, a higher proportion of patients with HPV+ head and neck cancers were male (87% vs. 77%), diagnosed at stage IV (75% vs. 66%) and non-Hispanic White (84% vs. 68%%); and a lower proportion of HPV+ patients were non-Hispanic Black (6% vs. 13%) and uninsured or had Medicaid coverage (13% vs. 25%). Overall, 5-year cancer-specific survival was higher among HPV+ patients (82%) than among HPV- patients (62%), with a wider disparity observed among Black head and neck cancer patients (HPV+ 74%, HPV- 44%). In multivariable models, significant differences in cancer-specific survival were found across racial/ethnic groups and HPV status (P-interaction: 0.045). Compared to White patients, persistent inequities in cancer-specific survival were observed among Black HPV+ (HR 1.49, 95% CI 1.19-1.87) and HPV- (HR 1.42, 95% CI 1.21-1.66); and among Latinx HPV+ patients (HR 1.32, 95% CI 1.03-1.69). Conclusions: In this population-based study of patients with head and neck cancers, significant disparities in cancer-specific survival were observed that differed by both race/ethnicity and HPV status. The complex inequities in outcomes of head and cancers likely reflect the clinical impacts of socioeconomic and demographic risk factors in addition to HPV-related dysregulation of tumor metabolism and the immune microenvironment.